Design of synthetic human gut microbiome assembly and butyrate production - Ryan L. Clark (Nature Portfolio, 2021)
Microbiomes designed with predictable functions could enable broad applications in health, agriculture and bioprocessing. Here the authors use a model-guided approach to design diverse synthetic human gut communities for production of the health-relevant metabolite butyrate.